Estimation of Logistic Regression Model on The Risk of Acute Respiratory Infection Toddlers at Cikampak Torgamba Public Health Center Using The Maximum Likelihood Method - Dian Maya Sari; Fibri Rakhmawati; Hendra Cipta (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2022)
According to the World Health Organization (WHO), the incidence of Acute Respiratory Infections (ARI) in the world by number of toddler who died achieve ± 13 million each year. Researchers will estimate the model equations logistic regression using maximum likelihood. The purpose of this study was to determine the logistic regression model against respiratory infection in infants and the test results of the method of maximum likelihood against respiratory infection in infants in the health center Cikampak Torgamba. Logistic regression Model against the toddler obtained results that the model to be used and the test results of the method of maximum likelihood that the model is significant.